(untitled) (PAMPA, 2025)
In recent decades, the intensification in the use of agrochemicals has generated complaints from different sectors of civil society regarding human and environmental health. In 1995, Santa Fe Province passed the Law 11273 on Pesticides and Fertilizers which rules the use of these products, however the fine tuning for local conditions was delegated to cities and towns through local ordinances of its own. From the perspective of complexity we propose to analyze the conflict dynamics over the use of agrochemicals from the practices of different local actors in Roldán, Santa Fe, Argentina. From the analysis applying the case study methodology, we identified three stages: installation of the problem, drafting and enactment of the ordinance, and implementation. We conclude that actors failed to construct a common meaning about the problem and that environmental conflict that characterizes the social relationships has produced new transformations in the peri-urban territory, evidencing the different conceptions of the society-nature relationship. We conclude that actors carry out different and coherent practices with the meanings attributed to the territory, reinforcing the environmental conflict that characterizes the relational plot, and in this way, the territory is constructed and transformed into a permanent tension